Performans produksi telur puyuh yang diberi ransum tepung limbah udang fermantasi - sukron latif; Edjeng Suprijatna; Dwi Sunarti (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2017)
This study was conducted to determine the effect the use of fermented shrimp  flour   waste (FSW) with different concentrations on the ration of the productivity of Japanese quail egg (Coturnix-coturnix japanica). This study used 250 female quails 8 weeks old. Research ingredients consist of corn, bran, soybean meal, shrimp flour, meat bone meal (MBM), lysin, methionin, lime, premix and FSW Shrimp waste consists of head, body skin and shrimp tail which is the rest of the shrimp stripping industry. The study design was using Complete Random Design (CRD) consisting of 5 treatments and 5 replications. The treatment unit consisted of T0 = Rations without TLUF, T1 = Ration using non fermented shrimp flour 7.5%, T2 = Ration using 5% TLUF, T3 = Ration using 7.5% TLUF and T4 = Ration using 10% TLUF. The data obtained were analyzed by using F test at 5% level, followed by Duncan test if any treatment effect. Parameters observed were feed consumption, hen day production (HDP), egg mass, feed conversion and income over feed cost (IOFC). The result of variance analysis showed that the treatment gave significant effect (P<0.05) to feed consumption and egg mass, while in HDP, feed conversion and IOFC did not show significant effect (P>0.05). The conclusion of this research is the use of fermented shrimp flour waste in quail ration can increase consumption, egg mass and IOFC but can not affect the production and conversion of feed. The highest IOFC value is in T2 treatment.